The Prevention of Thalassemia Revisited: A Historical and Ethical Perspective by the Thalassemia International Federation. (2nd January 2021) - Angastiniotis, Michael; Petrou, Mary; Loukopoulos, Dimitrios; Modell, Bernadette; Farmakis, Dimitrios; Englezos, Panos; Eleftheriou, Androulla
Abstract: Hemoglobinopathies are the most common monogenic disorders in humans; among them, thalassemia constitutes a serious medical and public health problem in high prevalence regions, in a geographical zone ranging from the Mediterranean Basin to China. In addition, migrations over the years have introduced thalassemia to many parts of the world. Although disease-specific programs are in place and accessible to most patients in prosperous countries, this is not the case in developing economies, where more than 75.0% of the patient population is born and lives; this concerns both prevention and treatment programs. In view of the significant improvements in public health and healthcare systems over the past few years, the Thalassemia International Federation has revisited the thalassemia prevention programs, initiatives and policies in some of its member countries, discussing their effectiveness and whether any changes in policy or public attitudes to thalassemia prevention have occurred through the recent years.